How Can Drug Metabolism and Transporter Genetics Inform Psychotropic Prescribing? - Carvalho Henriques, Beatriz; Yang, Esther H.; Lapetina, Diego; Carr, Michael S.; Yavorskyy, Vasyl; Hague, Joshua; Aitchison, Katherine J. (Frontiers in Genetics, 2020)
Many genetic variants in drug metabolizing enzymes and transporters have been shown to be relevant for treating psychiatric disorders. Associations are strong enough to feature on drug labels and for prescribing guidelines based on such data. A range of commercial tests are available; however, there is variability in included genetic variants, methodology, and interpretation. We herein provide relevant background for understanding clinical associations with specific variants, other factors that are relevant to consider when interpreting such data (such as age, gender, drug–drug interactions), and summarize the data relevant to clinical utility of pharmacogenetic testing in psychiatry and the available prescribing guidelines. We also highlight areas for future research focus in this field.